Factorial invariance of bias scale, Trait version, in engineering and social sciences Mexican university students - López Walle, Jeanette M.; Gastélum Cuadras, Gabriel; Chávez Guerrero, Alejandro; Rodríguez Villalobos, Judith Margarita; Castillo Fernández, Isabel María (2014)
This present study analyses the psychometric properties of BIAS (Body Image Anxiety Scale) testing, trait version, in engineering and social sciences students. A total sample of 918 participants; 460 from engineering and 458 from social sciences, with an average age of 18.27 years (DE = 0.70) and 18.13 years (DE = 0.74) respectively. Exploratory and confirmatory factorial analysis showed that a bi-factorial structure is feasible and convenient for both populations (engineering and social sciences) according to the established psychometric requirements because the students are the ones who provided the information. Furthermore the factorial structure, factorial loads and the intercepts are considered invariant in the engineering and social sciences areas; however there are differences in the mean of both factors among the two populations.